(untitled) (Journal of Kathmandu Medical College, 2017)
Background: Surgical complications represent a signifi cant cause of morbidity and mortality with the rate of major complications after inpatient surgery in industrialized countries. The purpose of this study was to summarize experience with surgical checklist use and efficacy for improving patient safety. Objective: To evaluate the compliance of implementation and outcome of World Health Organization Surgical checklist use in surgical practice at Kathmandu Medical College. Methods: This is a prospectively designed descriptive study including adult patients undergoing surgical procedure in Kathmandu Medical College Hospital from June 2013 till June 2014. Obtained data on compliance of World Health Organization safety checklist use by practitioner and its outcome in patient’s safety were assessed using SPSS version 15. The surgeries that underwent under local anesthesia were excluded from the study. Results: World Health Organization checklist was implemented in all 288 patients undergoing various surgical procedures with acceptable compliance by all 41 practitioners. Although it had no impact on correctable mortality and morbidity, frequent instrument malfunctions were offi cially recorded. Attitudes towards use of checklist was good as 100% of participants wanted use of checklist if they were having operation on themselves. However 22% of the participants complained of extra time needed to fi ll the checklist. Time taken to fi ll up sign in column of checklist was on average from 120 to 150 seconds (mean 135±5secs) and sign out was 80-100 seconds (mean 95±6secs). Only 69% of the participants were available for sign out. Scissor malfunction was detected in 4(1.38%) cases and operation theatre table related problem was found in one case (0.34%). Conclusion: Implementation of World Health Organization Surgical Safety Checklist can be done with acceptable compliance and instrumental malfunction was well documented.